Stabilization by Benzannulation: Butterfly Azaacenes - Müller, Matthias; Reiß, Hilmar; Tverskoy, Olena; Rominger, Frank; Freudenberg, Jan; Bunz, Uwe H. F. (Chemistry - a European journal, 2018)
Soluble butterfly-shaped tetraazapentacenes and tetraazaheptacenes were prepared by condensation or Stille coupling with a stannafluorene. The stability of the benzo-winged tetraazaheptacene is dramatically increased through the fourfold benzannulation, yet its acene character is retained to a significant extent.
Gesehen am 10.05.2019